Effectiveness of the APE-AI Model on Self-Efficacy in Managing the Risk of Sexually Abusive Behavior and Improving the Quality of Life Among Muslim Adolescents in the Deep South Thailand - แว, อวาทิพย์; แวหะยี, ฮูดา (Journal of Health Science of Thailand, 2024)
The objectives of this research and development were to study lifestyle causes of inappropriate sexual behavior and lifestyle of school-age mothers and to synthesize guidelines for taking care of school-age mothers so that they could lead a normal life. In addition, it was aimed to develop a risk management model for inappropriate sexual behavior and improvement of the quality of life of Muslim adolescents in the three southern border provinces; as well as to assess the level of self-efficacy in managing the risk of inappropriate sexual behavior and improving the quality of life. Study samples were 30 students for in-depth interview. Focus group discussion were conducted among 30 informants. Research instruments were a model to manage the risk of sexually inappropriate behavior and improve the quality of life of adolescent mothers in the three southern border provinces (APE-AI Model) and the self-efficacy level scale for risk management of inappropriate sexual behaviors and quality of life improvement among Muslim adolescents. Validity of questionnaire was tested using item-objective congruence Index, yielding a value of 0.86. Reliability was tested using Cronbach’s alpha coefficient, yielding a value of 0.89. Data were analyzed using Paired t-test. The results showed that lifestyle reasons for having children at school age were caused by parents who did not understand and did not have time for the adolescents, lack of knowledge and skills about safe sex, improper use of technology media, the use of religious principles to solve sexual behavior problems (Haram), lack the opportunity to continue education, and insufficient income to cover expenses. A risk management model for inappropriate sexual behavior and improving the quality of life of adolescent mothers was developed which incorporated the context of the southern border region. It consisted of decision-making skills improvement and appropriate coping mechanism (self-efficacy), receiving help from family. experts and related agencies, developing safe sex knowledge and skills and sharing experiences on sexual behavior, impact, and roles of adolescent mothers. After the implemmentation, the students had a significant increase in the level of self-efficacy in managing the risk of inappropriate sexual behavior. and improving the quality of life (p<0.05). Therefore, the developed model could be used in educational institutions to prevent teenage pregnancy and inappropriate sexual behaviors of adolescents within a Muslim cultural context.